Unintentional injuries and the home environment: a qualitative study. (7th October 2012) - Ablewhite, J; Kendrick, D; Watson, M; Shaw, I
Abstract : Background: Childhood unintentional injury is a leading cause of death and disability in the UK. Aims: To gain an understanding of parental perceptions of child unintentional injury risks, safety practices including parental supervision and implementation of safety information/advice. To explore reasons for inequalities in unintentional injury rates in children aged 0–4 years. Methods: Qualitative interviews with parents of a child aged 0–4 years; 16 with mothers living in an area of socio-economic disadvantage and 21 with mothers living in an area of relative affluence. Thematic analysis was used to analyse the data. Results: Low income mothers living in disadvantaged areas are not less aware of child home injury risks. Some parents perceive the risk of child injury based on their own experiences with their child rather than describing child injury risks with a more general awareness. Parents from both groups perceive a difference between 'acceptable' versus 'unacceptable' unintentional injuries. Parents do not seek to prevent 'acceptable' unintentional injuries. Listening is used as a supervision strategy for boys more than girls. Older children as supervisors of siblings are perceived differently by parents from different social groups. Parents living in circumstances of socio-economic disadvantage face greater barriers to adapting their homes. Parents living in disadvantaged areas describe a fear of talking to professionals due to a fear of the consequences. Contribution to the Field: Few qualitative studies have investigated childhood unintentional injury by exploring differences between parents living in different socio-economic groups, in order to generate explanations for differential injury rates.